"Identity Formation or Knowledge Shopping"? Quality Reform in Malaysian Higher Education Governance - Quddus, S. M. Abdul (2012)
The term “knowledge society” has evolved the increasing amount of new ideas and rapid changes in economy, society and of course culture. Education has been playing the key roles in promoting discovery, innovation and development; the practitioners of expertise are the agents and carriers of knowledge society. Following the introduction of a more commercially oriented ethos in the higher education sector in Malaysia, increasing attention has been paid to “knowledge shopping” i.e. user satisfaction and value for money (Ismail and Musa, 2007). This trend is driven by an ideological shift from planning to quasi-markets in higher education as well as ideas of a stronger role for the students in terms of students’ rights and more individualized service levels. Malaysia has been implementing series of reform, called the quality reform, which follows a standard set to achieve national objectives e.g. 10th Malaysia Plan and “Vision 2020”. Malaysia is most eager to be a regional education hub (Sirat, 2007). The governance literature would be considered as the theoretical underpinning of this study. The aim of this study is to explore how standards, as governance forms are used and what role it gets in the globalization process of Malaysian higher education. Higher educational institutions in Malaysia have been implementing almost a blueprint of the national standard of education in line with “Vision 2020”. In trying to understand what role standards will have in the globalization process an interesting questions is; whether the use of standards bring the higher education system in Malaysia in the direction towards a knowledge society i.e. “identity formation” or, more accurately, in a direction towards a global market i.e. “knowledge shopping”?